Impact, Legitimacy, and Limitations of Truth Commissions - Nichols, Angela D. author. aut Link
XV, 106 p. 7 illus., 3 illus. in color.
Keywords: “The study of transitional justice has moved beyond a normative understanding of impact driven by dichotomous understandings of implementation. Nichols’ book and dataset are important contributions to this new work. Advancing our knowledge of the legitimacy of truth commissions, her findings have important implications for how we study, and advocate for, transitional justice moving forward.” —Cyanne E. Loyle, Indiana University, USA, and Peace Research Institute Oslo (PRIO), Norway This book develops a theoretical understanding of how truth commissions achieve legitimacy and contribute to peace and stability. Angela D. Nichols argues that truth commissions are most likely to impact society when they possess certain institutional characteristics—characteristics that send important political signals to the state and broader society alike. If these signals suggest greater degrees of authority, a break with the past, and transparency in both its investigations and its findings, the truth commission is more likely to impact society. In particular, Nichols examines whether or not states that adopt truth commissions with these characteristics are more likely to respect human rights and experience lower levels of violence. She concludes with an analysis of Colombia’s newly established Truth, Coexistence, and Non-Recurrence Commission. Angela D. Nichols is Assistant Professor in the Department of Political Science at Florida Atlantic University, USA. She has published work in the Journal of Conflict Resolution; International Studies Perspectives; Conflict, Security, & Development; and Civil Wars. .